2015
DOI: 10.1007/s12630-014-0305-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative awareness risk, anesthetic sensitivity, and anesthetic management for patients with natural red hair: a matched cohort study

Abstract: Purpose The red-hair phenotype, which is often produced by mutations in the melanocortin-1 receptor gene, has been associated with an increase in sedative, anesthetic, and analgesic requirements in both animal and human studies. Nevertheless, the clinical implications of this phenomenon in red-haired patients undergoing surgery are currently unknown. Methods In a secondary analysis of a prospective trial of intraoperative awareness, red-haired patients were identified and matched with five control patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…22 ont évalué différentes mesures de la sensibilité aux anesthésiques dans une cohorte prospective de patients. Ils ont trouvé que les roux et un groupe apparié de patients contrôles avaient reçu des quantités semblables d'anesthésiques volatils, d'opioïdes et d'adjuvants anesthésiques.…”
Section: Les Roux Et Les Anesthésiquesunclassified
See 2 more Smart Citations
“…22 ont évalué différentes mesures de la sensibilité aux anesthésiques dans une cohorte prospective de patients. Ils ont trouvé que les roux et un groupe apparié de patients contrôles avaient reçu des quantités semblables d'anesthésiques volatils, d'opioïdes et d'adjuvants anesthésiques.…”
Section: Les Roux Et Les Anesthésiquesunclassified
“…Subjects with the mutation were also more than twice as likely to avoid dental care as participants without MC1R gene variants, even after controlling for general trait anxiety and sex. 21 In this issue of the Journal, Gradwohl et al 22 describe a secondary analysis of patients drawn from a previously published study of anesthetic awareness in patients at high risk for recall. 23 In their current analysis, the investigators compared four anesthetic characteristics in 319 self-reported redheads and 1,595 propensity-matched patients with other hair colours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Other genetic factors such as gender, ethnicity and hair colour are also associated with pain sensitivity. [21][22][23] For instance, female gender and people of younger age were found to be associated with higher post-operative pain scores. 17 Therefore, these factors must be considered when planning postoperative medication plans.…”
mentioning
confidence: 99%
“…analgesia", "adverse drug reaction". Se analizaron todos los artículos desde 1985 hasta (1)(2)(3)(4)(5). Hace más de una década hubo trabajos que apoyaron esta teoría de una diferente sensibilidad a los anestésicos, sin embargo no ha sido confirmada por los trabajos recientes.…”
unclassified